2016
DOI: 10.1177/2042018816652059
|View full text |Cite
|
Sign up to set email alerts
|

β-cell replacement sources for type 1 diabetes: a focus on pancreatic ductal cells

Abstract: Thorough research on the capacity of human islet transplantation to cure type 1 diabetes led to the achievement of 3-to 5-year-long insulin independence in nearly half of transplanted patients. Yet, translation of this technique to clinical routine is limited by organ shortage and the need for long-term immunosuppression, restricting its use to adults with unstable disease. The production of new bona fide β cells in vitro was thus investigated and finally achieved with human pluripotent stem cells (PSCs). Besi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 166 publications
(235 reference statements)
1
6
0
Order By: Relevance
“…Transplantation of mesenchymal stem cells was considered slowing the progression of diabetes and therefore allowing recovery of pancreatic cells. Also, β-like cells could be acquired from embryonic stem cell or induced pluripotent stem cells by stepwise differentiation [2, 3, 11, 29, 3137]. Other studies demonstrated that cells from the liver, skin, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of mesenchymal stem cells was considered slowing the progression of diabetes and therefore allowing recovery of pancreatic cells. Also, β-like cells could be acquired from embryonic stem cell or induced pluripotent stem cells by stepwise differentiation [2, 3, 11, 29, 3137]. Other studies demonstrated that cells from the liver, skin, etc.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that budding of new islets from ductal epithelium is not only a feature of embryonic pancreatic development, but also happens during pancreatic regeneration following pancreatic injury in adults. Therefore, many efforts have been taken to regenerate β cells from cultured pancreatic ductal cells 38, 69, 71 . One of the first successful attempts comes from Ramiya et al , in which the authors have isolated ductal epithelial cells from non-obese diabetic (NOD) mice, cultured them in vitro , and differentiated them into islet-like structures 72 .…”
Section: Regenerating β Cells From Stem Cells—in Vitro β Cell Regenermentioning
confidence: 99%
“…The most promising way for curing diabetes is islet transplantation, mostly focused on T1DM patients (Kuise and Noguchi, 2011), but donor shortage and life‐long need for immunosuppressive drugs make it less feasible for a routine clinical procedure (Benthuysen et al, 2016). Given these difficulties, over the last three decades, various methods have been attempted to regenerate/replace functional β cells in diabetic patients (Corritore et al, 2016; Aguayo‐Mazzucato and Bonner‐Weir, 2018; Zhou and Melton, 2018; Ghani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%